indonesia ANALISIS NILAI KUAT TEKAN BETON AKIBAT SUBTITUSI METAKAOLIN DENGAN VARIASI METODE PERLAKUAN PERAWATAN BETON - Salsabilla, Nadya Shafira; Hermawan , Okky Hendra; Utami, Miranti Yulinaningtyas (Teknik Sipil, Fakultas Teknik Universitas Negeri Jakarta, 2025)
The hot weather affecting Indonesia has become a major concern for the public. This study aims to compare the compressive strength values of concrete at 14 and 28 days, with variations in metakaolin substitution for cement (0%, 5%, 10%) and different curing methods. The experimental method and SPSS'22 statistical analysis were used in the research to evaluate the effect of curing at room temperature and in the open field on concrete. The study compared concrete curing treatment methods at room temperature and in the open field, with variations of metakaolin substitution (0%, 5%, 10%) in concrete with a quality of F’c 16 MPa. The concrete compressive strength results at 14 days: 16.5 MPa, 16.7 MPa, 16.4 MPa, 16.7 MPa, 15.7 MPa, 15.5 MPa. The concrete compressive strength results at 28 days: 16.5 MPa, 16.9 MPa, 15.9 MPa, 17.8 MPa, 17.4 MPa, 16.5 MPa. The statistical effect using SPSS with multiple linear regression testing shows the significance of the effect of variable X on variable Y in the 28-day concrete samples. Keywords : Metakaolin, Concrete Curing, Concrete Compressive Strength